Policy solutions for economic growth in a developing country : perspectives on Afghanistan's trade and development - Wani, Nassir Ul Haq (Emerald Publishing Limited, 2024)
Following the recent change in regime, Afghanistan is at a crossroads. Key to its stability is economic growth and international trade, yet many obstacles stand in its way. In Policy Solutions for Economic Growth in a Developing Country, author Nassir Ul Haq Wani outlines these challenges and offers clear policy solutions that will put the country on a path to revive, regenerate, and revitalize its economy. Further, he contextualizes Afghanistan within the region, giving greater insight into the needs of other developing countries. This in-depth study analyses the trading platform at national, international and regional levels for initiating a consistent and sustainable set of policies to promote exports. Alongside macroeconomic stability, this study argues that private sector development, technological progress, socio-economic balance, trade liberalization and a reinvigoration of exports can play an effective role in wealth creation for Afghanistan. Perspectives on Afghanistan's Trade and Development offers a rich and varied policy analysis for those who wish to design a policy to bolster exports from Afghanistan, and for academicians, researchers and students who wish to gain greater insight into this developing economy.